Strategi Pengembangan Sanitasi Sub Sektor Air Limbah Domestik Dengan Matriks IFAS dan EFAS Di Kabupaten Sekadau: Sanitation develpoment Strategy, Domestic Wastewater - GUNAWAN, IVAN ANDRI; Anggraini, Ika Muthya; Marbun, Julianti (Fakultas Teknik Universitas Panca Bhakti, 2024)
In formulating the sanitation development strategy, the SWOT analysis method is used which considers internal environmental conditions and external environmental conditions through a multi-aspect analysis approach (technical aspects, institutional aspects, regulatory aspects, funding aspects and community participation aspects). The SWOT analysis compares external factors of opportunities and threats with internal factors of strengths and weaknesses. Internal factors are entered into a matrix called the internal strategic factor matrix or IFAS (Internal Strategic Factor Analysis Summary). External factors are entered into a matrix called the external strategic factor matrix EFAS (External Strategic Factor Analysis Summary). Based on the results of the analysis, it can be concluded that the value of the strength aspect is 2.87, the weakness aspect is 3.30, the opportunities aspect is 2.97, and the threats aspect is 2.6. The results of these internal factors are at a value of -0.43, and the external factors are at a value of 0.37. The results of these two factors are displayed in a quadrant with coordinate values ​​(-0.43, 0.37) where X is an internal factor and Y is an external factor. Based on the analysis results, it shows that the position of the Domestic Wastewater sector is in the